Comparison of blood plasma and gelatin solution in resuscitation of children with dengue shock syndrome - Suryadi Nicolaas Napoleon Tatura; Novie Homenta Rampengan; Jose Meky Mandei; Ari Lukas Runtunuwu; Max FJ Mantik; Tony Homenta Rampengan (Indonesian Pediatric Society, 2009)
Background Dengue shock syndrome (DSS) is characterized bysevere vascular leakage and hemostasis disorder. It is the cause of death in 1 to 5 percent of cases. WH 0 management guidelines for resuscitation remain empirical rather than evidence-based.Objective To find out the alternative fluids to replace plasmaleakage in DSS.Methods We performed a prospective study and randomizedcomparison of plasma and gelatin solution for resuscitation ofIndonesian children with DSS. We randomly assigned 25 subjectswith DSS to receive plasma and 25 children to receive gelatinfluid. Statistical analyse were performed using chi-square test,Fisher's exact test, t test, Mann-Whitney test.Results The increment of pulse pressure width and the decrement of hematocrit in subjects treated with gelatin were higher than that of plasma atfour-hour therapy (P=0.002 and P=0.017). Only one patient died caused by unusually manifestation of DSS. The increment of body temperature in subjects treated with plasma was higher than that of gelatin at four-hour therapy (P=O.Oll). The decrement of platelet count in subjects treated with gelatin were less than that of plasma (P=0.018). The increment of diuresis rate in subjects treated with gelatin was higher than that of plasma at twenty-hour therapy (P<O.OOOl). The decrement of respiratory rate in subjects treated with gelatin was higher than that of plasmaat twenty-eight hour therapy (P=0.018). There was no differencein studied variables : total volume rate, blood pressure, pulse rate, re-shock rate, clinical fluid overload, allergy reactions, bleeding manifestations, and length of stay (P>0.05).Conclusions Gelatin solution can be used as volume replacementin resuscitation of DSS if blood plasma is not available especiallyat four-hour therapy.